Urolithiasis complicated by chronic obstructive pyelonephritis in patients with concomitant diseases of the cardiovascular system - R. V. Royuk; S. K. Yarovoy; R. A. Khomov (Исследования и практика в медицине)
Purpose of the study. To study the features of chronic obstructive pyelonephritis in patients with recurrent nephrolithiasis and concomitant diseases of the cardiovascular system.Materials and methods. The study included a total of 618 patients suffering from recurrent nephrolithiasis complicated by ChOP. The 3 groups were formed: the first (I) of them included 42 patients with ChOP and uncomplicated coronary heart disease (CHD); the second (II)- 38 patients with CHD complicated by chronic heart failure (CHF); III (control) group consisted of 24 respondents with recurrent urolithiasis.Results. The sample was dominated by men (78 %). In total, there were 474 (76.7 %) patients with intact cardiovascular system. Cardiovascular disease (CVD) suffered from 144 (23.3 %) patients, 38 (26.4 %) of whom had CHF of varying severity. Exacerbations of ChOP in patients of group I developed 1.5 times more often (once in 2.8-3 years) than in patients from the control group (on average after 18 months versus 28), and in group II almost annually (1 time in 13 months). In the entire cohort (n = 618), pyelonephritis was transformed into purulent-destructive in 19 (3.1 %) cases; with concomitant CVD, this complication developed in 7 (4.9 % of 144) cases, the remaining 12 (2.5 % of 474) respondents did not suffer from CVD. In group II, the purulent-destructive form occurred in 4 (10.5 %) patients; their share in the general group of patients with CVD was 2.8 % (the differences were significant - p < 0.05). Of the 19 patients with purulent-destructive pyelonephritis on the background of nephrolithiasis, more than a third (7 people - 36.8 %) had concomitant CHD, and of the 7 patients with this terrible complication that developed on the background of concomitant CHD, more than half (4 people - 57.1 %) had CHF of varying severity. The chemical composition of the urine samples was determined using a NICOLET iS10 spectral analyzer (Thermo scientific, USA). The stages of CHF were determined in accordance with the Strazhesco-Vasilenko classification [N. D. Strazhesco, V. H. Vasilenko, 1935]. Statistical data processing was carried out using the SPSS program 19. Absolute and relative indicators were calculated, as well as the exact Fisher criterion, taking into account the Bonferroni correction; the differences were considered reliable at p < 0.05.Conclusion. in patients with recurrent nephrolithiasis and concomitant CVD (especially with complicated CHF), exacerbations of obstructive pyelonephritis develop more often, the inflammatory process often turns into a purulent-destructive form.